Effects of school-based interventions on all 24-hour movement behaviours in young people: a systematic review and meta-analysis of randomised controlled trials - José Francisco López-Gil; Javier Rodrigo-Sanjoaquín; Miguel Ángel Tapia-Serrano; Javier Sevil-Serrano (BMJ Open Sport & Exercise Medicine)
Objective This systematic review and meta-analysis examined the effects of school-based interventions on all 24-hour movement behaviours.Design Systematic review and meta-analysis.Data sources Studies published in English, French, and Spanish from four databases from inception to February 2024 were identified.Eligibility criteria for selecting studies Eligible articles were randomised controlled trials (RCTs) that targeted and assessed physical activity (PA), sedentary behaviour (SB) and sleep duration among school-aged youth (3–17 years). Risk of bias and quality assessment were assessed using the Risk of Bias Tool 2 and Quality Assessment of Controlled Intervention Studies tool, respectively. Grading of Recommendations, Assessment, Development and Evaluation (GRADE) tool evaluated the certainty of evidence. The study was registered in International Prospective Register of Systematic Reviews (PROSPERO) (ID: removed for peer review).Results Of the 5141 records initially identified, 41 studies remained for full-text review. After full reading, 7 RCTs, comprising 8234 participants (49% girls), were included. Results indicated no effect in PA-related outcomes (Hedge’s g=0.12, –0.05 to 0.28), a small reduction in SB-related outcomes (g=−0.33, –0.51 to −0.16) and a small increase in sleep duration (g=0.30, 0.16 to 0.43) according to Hedges’ g (small effects (0≤g ≤0.50)). The GRADE, risk of bias and quality assessment tools indicated that most of the studies have a low risk of bias and are of good quality.Conclusions More school-based interventions promoting all movement behaviours are needed to determine if schools are optimal for encouraging 24-hour movement behaviours among young people.